Case report: A case of primary angiitis of the central nervous system: misdiagnosed for 3.5 years - Qin, Lixia; He, Miao; Lu, Wei (Frontiers in Neurology, 2023)
Introduction Primary angiitis of the central nervous system (PACNS) is an uncommon inflammatory condition that exclusively affects blood vessels within the brain parenchyma, leptomeninges, and spinal cord. Due to its infrequency and the variability in its clinical presentation and imaging findings, diagnosing PACNS can be challenging.In this study, we present the case of a teenager who initially presented with headaches and epilepsy. Comprehensive laboratory tests yield normal results. A series of brain magnetic resonance imaging (MRI) revealed a progression of changes, starting from localized cerebral atrophy and culminating in the development of a contrast-enhanced mass with vasogenic edema. Immune-associated encephalitis and mitochondrial encephalopathy were suspected, but immunologic investigations, mitochondrial DNA (mtDNA) and nuclear DNA (nDNA) sequencing using biopsied muscle, and muscle pathologies were all negative. Ultimately, a diagnosis of PACNS was confirmed through a stereotactic brain biopsy, which took place 3.5 years after the onset of symptoms. The patient responded favorably to treatment with glucocorticoids and cyclophosphamide.In summary, we have described a case of PACNS characterized by localized cerebral atrophy and tumor-like MRI findings, who was misdiagnosed as immune-associated encephalitis or mitochondrial encephalopathy for 3.5 years. We emphasize the importance of dynamic observation of MRI changes, as well as brain biopsy.